(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Acmella ciliata (Kunth) Cass., a medicinally important plant in the family Asteraceae, contains many phytochemicals like alkaloids, tannins, saponins, flavonoids, including a highly important alkylamide ‘Spilanthol’ which accounts for most of its pharmacological applications. The plant has rich commercial value because of its traditional phytomedicinal uses. The present study focused on the anticancer potentiality of cell biomass of A. ciliata obtained through cell suspension culture. The purplish friable callus raised in MS medium containing 0.5 mgl-1 BA and 1.0 mgl-1 NAA were cultured in liquid MS medium with same hormone combination. The cells after 28 days of culture were collected and quantification of spilanthol using high performance liquid chromatography (HPLC) revealed that the harvested cells from cell suspension culture of A. ciliata recorded 173.702 μgg-1 spilanthol content in them. The analysis of antiproliferative effect of the methanolic extract of the cell biomass revealed that it is capable of inhibiting or reducing the growth of SK-MEL-28 cell lines and a lower concentration i.e., 24.144 μgmL-1 of extract was needed to inhibit the growth by 50%. The study suggested the effectiveness of the cell biomass extract for the inhibition of uncontrolled growth of this melanoma cells and thus throw light on the possibility of formulating an anti-cancerous drug from this resource thereby benefiting the pharmaceutical industry.